1988
DOI: 10.1016/0014-5793(88)80029-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor‐induced phosphoinositide hydrolysis Modulation by protein kinase C

Abstract: A short-term treatment with phorbol 12,13-dibutyrate (PDBu) was found to inhibit totally the epidermal growth factor (EGF)-stimulated phosphoinositide hydrolysis in A431 cells, whereas long-term pretreatment with PDBu, which is known to down regulate protein kinase C, induced a greater accumulation of the EGF-triggered inositol phosphate accumulation, particularly of Ins(1,3,4,5)P,. The increased Ins(l,4,5)P3/Ins(l,3,4,5)P, formation in the PDBu long-term pretreated cells was coincident with the increased Caz+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1988
1988
1991
1991

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The effects observed on intracellular Ca 2+ release are consistent with the reported inhibition by TPA of PLC and IP 3 formation [1,2,6,9,27,33,34]. At lower concentrations of TPA (10 -~~ M), only the plasma membrane handling of Ca z+ was affected as evidenced by a reduced duration of the [Ca2+]~ plateau.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The effects observed on intracellular Ca 2+ release are consistent with the reported inhibition by TPA of PLC and IP 3 formation [1,2,6,9,27,33,34]. At lower concentrations of TPA (10 -~~ M), only the plasma membrane handling of Ca z+ was affected as evidenced by a reduced duration of the [Ca2+]~ plateau.…”
Section: Discussionsupporting
confidence: 78%
“…In quin-2 loaded A431 cells a short 5-10 rain treatment with TPA inhibits EGFinduced changes in [Ca2+];, suggesting that activation of PKC inhibits Ca 2+ entry [16]. Inositol phosphate production is also inhibited by 5-min treatment with TPA [33]. The same authors found treatment with phorbol ester for 24 hr resulted in an elevation of IP 3 and IP 4 production and elevation of [Ca2+]i [21].…”
Section: Introductionmentioning
confidence: 49%
See 2 more Smart Citations
“…Reentry of quiescent cells into the cell cycle, and subsequent division, is thought to occur in response to growth factor binding to specific cell surface receptors that initiates a cascade of signal transduction events. These events include an activation of tyrosine-specific protein kinases (Hunter and Cooper, 1985;Zippel et al, 1986;Alexander and Cantrell, 19891, an activation of phospholipase C leading to an increased breakdown of phosphoinositides and the generation of inositol 1,4,5-trisphosphate and diacylglcerol (Hart et al, 1988;Vicentini et al, 1988;Berridge and Irvine 19891, and a concomitant elevation of cytosolic Cad+ from intracellular stores or by cellular uptake (Moolenaar et al, 1983;Rozengurt, 1986;Housley et al, 1988).…”
mentioning
confidence: 99%